2020
DOI: 10.1007/s11538-020-00710-5
|View full text |Cite
|
Sign up to set email alerts
|

Decoys and Dilution: The Impact of Incompetent Hosts on Prevalence of Chagas Disease

Abstract: Biodiversity is commonly believed to reduce risk of vector-borne zoonoses. However, researchers already showed that the effect of biodiversity on disease transmission is not that straightforward. This study focuses on the effect of biodiversity, specifically on the effect of the decoy process (additional hosts distracting vectors from their focal host), on reducing infections of vector-borne diseases in humans. Here, we consider the specific case of Chagas disease and use mathematical population models to obse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Here, we consider a model with a single vector-host population for the transmission of T. cruzi between triatomines and peridomestic dogs. Like most Chagas disease models [35,43,45,46,51,58], here we ignore the impact of seasonality on triatomine dynamics by assuming all model parameters to be constant over time. We used an age-structured model for the triatomine population (Fig 1).…”
Section: Single Vector-host Population Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we consider a model with a single vector-host population for the transmission of T. cruzi between triatomines and peridomestic dogs. Like most Chagas disease models [35,43,45,46,51,58], here we ignore the impact of seasonality on triatomine dynamics by assuming all model parameters to be constant over time. We used an age-structured model for the triatomine population (Fig 1).…”
Section: Single Vector-host Population Modelmentioning
confidence: 99%
“…Such efforts have identified reducing domestic vectorial transmission as key to reducing the incidence of Chagas disease in humans [43,44]. Further, housing animals-including dogs-in homes has been linked to an increased risk of T. cruzi infection in humans [4,45,46,47,48,49,50].…”
Section: Introductionmentioning
confidence: 99%
“…During our literature review, we did not find any value for infection rates of leptospirosis in cattle and in humans (β lc and β lh respectively). Hence, we follow the method used in [20,19] to estimate β lc and β lh which gives…”
Section: Parameter Estimationmentioning
confidence: 99%
“…Hence, the presence of cattle increases host richness in the setting, which might eventually reduce the combined burden of these two diseases for humans. Earlier studies showed that an additional host (host richness) in a setting helps to reduce human infections of vector-borne diseases if certain conditions are maintained [16,17,18,20]. Johnson and Thieltges in 2010 identified that host diversity may help to reduce human infections depending on the relative abundance of additional host(s) relative to the focal host [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation